The Relationship Between Midwife Communication And The Level Of Satisfaction Of Pregnant Women In Antenatal Care Services At The Puskesmas Padang Ulak Tanding - Rahmadiana, Sinta; Anissa, Kintan; Rossita, Taufianie (Universitas Dehasen Bengkulu, 2025)
During pregnancy, regular supervision or examination is required or better known as Antenatal Care (ANC). Antenatal Care is the most important thing of pregnancy, by checking pregnancy regularly, it is hoped that it can detect conditions that contain risks in pregnancy and / or childbirth for both the mother and the fetus. Good communication between midwives and pregnant women greatly affects the satisfaction of pregnant women in receiving services by midwives. So that mutual trust between midwives and patients can be obtained. The purpose of this study was to determine the relationship between midwife communication and the level of satisfaction of pregnant women in Antenatal Care services. The method in this study is descriptive correlative with a cross sectional approach. The sample was 40 people using total sampling technique. Data analysis using chi square test.The results of this study indicate that there is a relationship between midwife communication and the satisfaction of pregnant women in ANC services with a P-value = 0.000. The results of this study are expected to increase self-awareness to pay more attention to the health conditions of the womb by conducting ANC visits according to standards.